Analisis Realisasi Anggaran Pendapatan dan Biaya pada CV.Berkah Ananda di Samarinda - mirza dicky setyawan (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2018)
Mirza Dicky Setyawan. Budget Analysis and Realizations of Earned and Cost towards CV. Berkah Ananda of Samarinda, tutored by Mr. Agus Iwan Kesuma as the first advisor, and Mrs. Ferry Diyanti as the second advisor.The objectives of this research are deliberately to find out the budget variance between budget and realization of earned and cost under coal production activities towards CV. Berkah Ananda of Samarinda on 2015, and to apprehend the causative factors of budget variance amongst budget and realization of earned and cost which befall on CV. Berkah Ananda on Samarinda.The analysis tool that used is budget variance analysis of earned budget which consists of; 1. Variance analysis of sales, 2. Variance analysis of trading value. While the variance analysis of budget comprises of; 1. Variance analysis of material cost, 2. Variance analysis of indirect labor cost, 3. Cost analysis of overhead factory.According to the analysis and research from above, overall it can be perceived that there is an unfavorable variance between budget and realization towards earned and also manufacturing cost in total Rp 31.743.748.584 on 2015, by sum up Rp 11.118.055.000 in the unfavorable variance from utilization quantity of material, Rp 759.856.500 in the unfavorable labor efficiency and cost variance, and Rp 5.010.704.512 in the unfavorable variance of manufacturing overhead cost. Thus, the motive of the unfavorable variance is happen because of the deficiency of management control function, with the result of causing loss.